Assessing the mid-term growth outlook for the Indian economy - Jamie Barker; Risto Herrala (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
Since embarking on economic reform in 1991, India has experienced three decades of rapid economic development. Recently, however, there has been significant uncertainty about the growth outlook of the Indian economy in the mid-term perspective. In this paper we use standard regression techniques to project the path of the Indian economy over the next 4 years. The analysis, which abstracts from the pandemic period, mainly serves as support to forecasting the global economy. After the pandemic, GDP growth is projected to rebound this year and then slide to-wards 6 ‒ 7% in the medium term. The analysis broadly agrees with the recent projections of India's mid-term growth rate by other institutions.
urn:nbn:fi:bof-202106141292
Keywords: 330; Indian economy; forecasting; GDP growth